Toward a Theory of Familiness: A Social Capital Perspective - Pearson, Allison W.; Carr, Jon C.; Shaw, John C. (Entrepreneurship Theory and Practice, 2008)
In the search for ways in which the family firm context is unique to organizational science, the construct of “familiness” has been identified and defined as resources and capabilities that are unique to the family's involvement and interactions in the business. While identification and isolation of a construct unique to family firms is both groundbreaking and important for family firm research, it is also important that the development of the construct continues to be examined from complementing theoretical viewpoints. As such, we set out to review the development of the familiness construct and identify its dimensions. We also explore the nomological relationships of the construct based on a social capital theory perspective and offer a theory of familiness.